Perilaku Non-Suicidal Self-Injury Pada Gen-Z Remaja Kota Semarang: Identifikasi Dengan Inventori Mindfulness-Based Stress Reduction Dan Rasa Syukur - Nida, Izzatin; Sulastri, Augustina; Suparmi (ANIMA Indonesian Psychological Journal, 2026)
Non-suicidal self-injury (NSSI) is a serious mental health problem among late adolescents of Generation Z (Gen-Z). However, the role of positive psychological factors such as mindfulness-based stress reduction (MBSR) and gratitude as statistical predictors of non-suicidal self-injury (NSSI) has not been widely explored empirically in Indonesia. This study aims to test whether mindfulness-based stress reduction (MBSR) and gratitude can statistically predict non-suicidal self-injury (NSSI) in Generation Z (Gen-Z) in Semarang City, both partially and simultaneously. The term "predictor" here is used in a statistical sense, and not in a causal relationship. This quantitative study involved 143 university students aged 18–22 years old, selected using convenience sampling techniques. Data collection utilized adapted instruments, namely: (1) mindfulness-based stress reduction questionnaire (MBSR; adapted from Fatemi et al., 2024; Liu et al., 2025), ); (2) gratitude questionnaire (adapted from Fekete & Deichert, 2022; Tachon et al., 2021); and (3) non-suicidal self-injury (NSSI) scale (adapted from Faura-Garcia et al., 2021; Poudel et al., 2022). The results of the analysis showed that mindfulness-based stress reduction (MBSR) significantly predicted positive non-suicidal self-injury (NSSI; β = 0.295; p = 0.002), while gratitude significantly predicted negative non-suicidal self-injury (NSSI; β = -0.370; p < 0.001). The overall regression model was significant (F = 8.243; p < 0.001) with an R2 of 0.105. These findings reveal a complex dynamic where mindfulness-based stress reduction (MBSR), without adequate acceptance skills, can actually statistically increase vulnerability to non-suicidal self-injury. (NSSI), while gratitude has been shown to be a strong protective factor. This study recommends the integration of gratitude components into non-suicidal self-injury (NSSI) prevention programs and a cautious approach in implementing mindfulness interventions for vulnerable populations.